2015
DOI: 10.1371/journal.pntd.0004215
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Malaria Resurgence in Greece through the Association of Mass Drug Administration (MDA) to Immigrants from Malaria-Endemic Regions and Standard Control Measures

Abstract: Greece was declared malaria-free in 1974 after a long antimalarial fight. In 2011–2012, an outbreak of P. vivax malaria was reported in Evrotas, an agricultural area in Southern Greece, where a large number of immigrants from endemic countries live and work. A total of 46 locally acquired and 38 imported malaria cases were detected. Despite a significant decrease of the number of malaria cases in 2012, a mass drug administration (MDA) program was considered as an additional measure to prevent reestablishment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…The identification of the same haplotypes as in an earlier study, in which a combination of only 3 markers were used to analyze samples from 2 consecutive years (2011 and 2012), suggested that sustained transmission in the area was possible and further measures were needed to control the disease. Thus, mass drug administration with the immigrant population in Laconia was decided on and performed as a supplementary measure ( 12 ). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of the same haplotypes as in an earlier study, in which a combination of only 3 markers were used to analyze samples from 2 consecutive years (2011 and 2012), suggested that sustained transmission in the area was possible and further measures were needed to control the disease. Thus, mass drug administration with the immigrant population in Laconia was decided on and performed as a supplementary measure ( 12 ). …”
Section: Discussionmentioning
confidence: 99%
“…The prompt and flexible countermeasures brought to bear by the Greek public health infrastructure were effective in containing and then extinguishing the foci of transmission ( 12 ). In our genotypic analyses, we highlight 2 epidemiologic features: first, the high potential for imported P. vivax to establish sustainable transmission within a short time; and second, the difficulty in predicting the locations where such transmission might occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 On the basis of this analysis of the natural environment, other areas of Greece that are equally environmentally suitable for potential transmission were targeted for indoor residual spraying, aerial sprayings, provision of long-lasting insecticide-treated nets, active case detection, and mass drug administration; transmission was subsequently interrupted in 2013 and 2014. 52 Waterborne IDTEs are another area of public health concern. Swimming in warm brackish water can result in infections caused by Vibrio species other than Vibrio cholera, and these infections can be serious, particularly for immunocompromised individuals.…”
Section: Natural Environmentmentioning
confidence: 99%